Parapsilorhynchus alluriensis, a new species of cyprinid fish (Teleostei: Cyprinidae) from the Eastern Ghats, of India - Jadhav, S. S.; Karuthapandi, M.; Chandra, Kailash; Jaiswal, Deepa; Dinesh, K. P.; Narahari, A. (Zootaxa, 2020)
A new species of cyprinid fish, Parapsilorhynchus alluriensis, is described from the Alluri Hills of Andhra Pradesh State, India. It is distinguished from its congeners by the combination of the following characters: A poorly-developed callous pad present behind lower lip; head deep (depth at occiput 47.3–72.3% head length, HL); body stout and deep (depth at dorsal fin origin 17.3–21.7 % standard length, SL); gape width 27.3–32.8% HL; inter-orbital space 33.9–43.2% HL; lower lip rounded; mouth opening situated very close to the anterior tip of snout; upper lip concealed by a poorly-developed rostral fold which is slightly fringed; minute papillae on rostral fold; 3 simple pectoral-fin rays; 33–34 lateral-line scales. A partial phylogeny based on the DNA Barcode COI gene suggests a sister-group relationship between the new species and P. prateri. Till date, the genus consists of four species from the Western Ghats, three from the Eastern Ghats, including the species described herein totaling it to seven from the peninsular India.